(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
This article examines the circumstances and dynamics of the assassination of Piersanti Mattarella, President of the Sicilian Regional Government, who was killed in Palermo on 6 January 1980. Adopting a multidisciplinary framework, it juxtaposes classical sources (judicial memoirs, contemporary reportage) with the records of the second criminal trial concerning the masterminds of the Bologna massacre (2 August 1980). The study asks whether the complex nexus of interests underlying the killing should be understood as part of a broad subversive network or—consistent with the recent investigative orientation of the Palermo Public Prosecutor’s Office—reframed within a strictly Mafia context. Preliminary results demonstrate that the chosen interpretive lens shapes not only the historical narrative but also the design of operational countermeasures.